Spatiotemporal dynamics of ecosystem services and ecological zoning in rapidly urbanizing eastern Guangdong - Wu, Wenkun; Yang, Huajie; Wei, Lisha; Fang, Zhongjian; Liu, Xiaodong (Frontiers in Earth Science, 2025)
Ecosystem services (ESs) in rapidly urbanizing regions are undergoing significant spatiotemporal changes driven by urban sprawl. However, existing studies have insufficiently addressed the heterogeneity of ESs, particularly the dynamic interactions between ecological processes and regional environmental conditions. This study focuses on eastern Guangdong, China, and quantifies four key ESs—carbon storage (CS), habitat quality (HQ), soil retention (SR), and water retention (WR)—from 2000 to 2020 using the InVEST model. The spatial heterogeneity of natural and socioeconomic drivers was examined through a multi-scale geographically weighted regression (MGWR) model. Ecological zones were delineated using Self-Organizing Map—Fuzzy C-Means (SOM-FCM) clustering, followed by zonal statistical analysis. Overall, ESs exhibited a declining trend over two decades, with SR and WR decreasing by 23.4% and 18.6%, respectively, while CS and HQ remained relatively stable. A distinct north–south gradient was identified, with stronger ES performance in the mountainous north. NDVI consistently showed the strongest positive influence in central regions; precipitation (PRE) and temperature (TEMP) fluctuated sharply in the north; population pressure peaked in the north and turned negative in the south by 2020; GDP had a positive effect in the east but a negative effect in the west; slope exerted the greatest influence in eastern areas; and the east–west elevation difference gradually weakened. Four ecological zones were identified: Protection, Conservation, Improvement, and Control. Between 2000 and 2020, Control Zones expanded significantly due to intensified urbanization, while the other three zones contracted. These findings highlight the urgent need for zone-specific strategies: strict conservation in Protection Zones, ecosystem restoration in Conservation Zones, ecological connectivity and low-impact use in Improvement Zones, and compact urban development in Control Zones. The proposed framework provides a transferable approach for capturing the spatial dynamics of ESs and supporting adaptive ecological management in fast-urbanizing regions.